Long-term outcomes of early posterior scleral contraction for myopic macular retinoschisis in patients up to 30 years - Linyan Zheng; Jian Zhao; Caiyu Yu; Liang Dong; Anquan Xue; Shuangqian Zhu (Frontiers in Medicine, 2026)
Aim To evaluate the long-term anatomical and functional outcomes of early posterior scleral contraction (PSC) in patients up to 30 years with myopic macular retinoschisis (MRS). Methods This retrospective study included 21 patients (27 myopic eyes) with MRS, with or without macular detachment, who underwent PSC and had a postoperative follow-up exceeding 2 years ( n = 27). Eyes with MRS underwent PSC, an extraocular procedure involving the placement of a genipin-crosslinked allogeneic strip at the posterior pole to shorten axial length and relieve vitreoretinal traction. Anatomical resolution of MRS, best-corrected visual acuity (BCVA), axial length change, were analyzed in patients with approximately 5-year follow-up records (the 13-eye main analysis cohort); while the overall safety profile was reported using the 27-eye descriptive cohort. Results At approximately postoperative year 5, complete resolution of MRS was achieved in 4 eyes (30.8%, 95% CI: 12.7%−57.6%), and partial resolution occurred in 9 eyes (69.2%, 95% CI: 42.4%−87.3%); BCVA did not improve significantly compared to the baseline level ( P = 0.482, n = 13). Mean axial length shortened significantly immediately postoperatively ( P < 0.001, n = 13) but gradually regressed to near baseline at approximately postoperative year 5 ( P = 0.183, n = 12). In the 27-eye descriptive cohort, no eye progressed to macular hole or retinal detachment, and metamorphopsia all resolved within 8 months. No sight-threatening intra- or postoperative complications, such as cataract, iatrogenic macular hole, were observed. Conclusion Early PSC may offer favorable anatomical stability and acceptable safety in young MRS patients. However, larger prospective controlled studies are needed to confirm its long-term efficacy and safety.